Evaluation of Daily Physical Activity Levels with Metabolic Holter in Adolescents - Abdullah Güllü (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to evaluate daily physical activity levels in adolescents, aged 11, 12 and 13 with metabolic holter. Totally 99 healthy and volunteer male students, aged 11-13 years, participated in this study. The participants were divided into three groups according to their chronological age: 11 age group (n: 35), 12 age group (n: 34) and 13 age group (n: 30). The physical activity levels of the children's were measured by SenseWear Armband (SWA) for 3 consecutive days (72 hours), in the absence of physical education class days. Height, weight, body mass index, daily total energy consumption, physical activity level, daily average number of steps (STEP), daily average length of stay and daily average sleep time were measured. The data obtained in the study were determined by one way ANOVA and multiple comparison test. P lt;0.05 was considered significant in all tests. There was a significant difference in the mean values of height (F=20.3; p=0.00), weight (F=12.55; p=0.00), and STEP (F=7.64; p=0.01) in the study group. The difference in height and weight mean was significant in favor of 13 age group (11 lt;12 lt;13, respectively) and STEP was in favor of 11 years (13≤12 lt;11, respectively). The differences between the remaining variables were not significant (p gt; 0.05). In this study, it was concluded that the adolescents who were in different age groups and did not have physical education classes, the duration of physical activity was low, but their duration of inactivity was high.